Urban Planning and the World Heritage List of Cities - Bahram Ghadiri (صفه)
The present article is the translation of the ninth chapter of "Management Guidelines for World Cultural Heritage Sites" by Bernard M. Feildon and Jukka Jokilehto, a book published in 1993 by the International Center for the study of the Preservation and Restoration of Cultural Property, Rome.It is evident that the application of the guidelines of this chapter, however abstract they may seem, open new frontiers for architects and those interested in this field.